1990
DOI: 10.1177/019262339001800303
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Gastric Mucosa of the Small Intestine in Laboratory Beagle Dogs

Abstract: Out of the 365 young laboratory beagle dogs which were used in 17 toxicity bioassays, 15 cases (4.1%) were diagnosed as having congenital heterotopic gastric mucosa of the small intestine. Its incidence in the male dogs (12 cases out of 187) was higher than in the female dogs (3 cases out of 178). Grossly, the lesions were seen as an ulcerous focus of the small intestine, 25 cm to 88 cm proximal to the ileocecal valve. All of the lesions were quite similar histologically and electron microscopically to the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The three cases of intestinal metaplasia and pyloric adenoma in the rectal HGM identified in the present review, [ 54 , 70 , 87 ] cancers from HGM in animals [ 96 ], and rare cancers from HGM in the esophagus [ 97 , 98 ], small bowel, gallbladder and colon in humans [ 97 , 99 , 100 ], suggest that HGM has a risk of malignancy. The present three cases of HGM with intestinal metaplasia and adenoma were incidentally diagnosed in asymptomatic adults during screening colonoscopy, and represent the 14% of adults ≥45 years and the 21% of all asymptomatic cases.…”
Section: Discussionmentioning
confidence: 98%
“…The three cases of intestinal metaplasia and pyloric adenoma in the rectal HGM identified in the present review, [ 54 , 70 , 87 ] cancers from HGM in animals [ 96 ], and rare cancers from HGM in the esophagus [ 97 , 98 ], small bowel, gallbladder and colon in humans [ 97 , 99 , 100 ], suggest that HGM has a risk of malignancy. The present three cases of HGM with intestinal metaplasia and adenoma were incidentally diagnosed in asymptomatic adults during screening colonoscopy, and represent the 14% of adults ≥45 years and the 21% of all asymptomatic cases.…”
Section: Discussionmentioning
confidence: 98%
“…Iwata and colleagues described a 4.1% (15/365 dogs) incidence of heterotopic gastric mucosa of the small intestine at necropsy of young Beagle dogs utilized for other research purposes . The grossly visible circular lesions, confirmed on histopathology to be heterotopic gastric mucosa, were located along the antimesenteric border of the ileum to jejunum, between 25 and 88 cm orad to the ileocecal valve.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported as an incidental finding in 4.1% of 365 research Beagles necropsied as part of a toxicology study. 1 Although it is not believed to frequently be associated with pathology, it has previously been found associated with cases of intestinal neoplasia, obstruction, and septic peritonitis secondary to diverticular rupture. 2,3 This report documents a case of surgically managed acute abdomen in a young dog secondary to abscess formation within a closed diverticulum of heterotopic gastric mucosa.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwata et al 35 reported that an incidence of ectopic stomach tissue in male Beagle dogs was 4.1% and 1.7% in females. In this study the inci dence of ectopic stomach tissue was 2.7% (2.2% in males, 3.1% in females), showing a lower incidence than that reported by Iwata.…”
Section: Non-neoplastic Lesionsmentioning
confidence: 99%